2017
DOI: 10.4103/ijccm.ijccm_257_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients admitted with hyponatremia in the medical intensive care unit

Abstract: Background and Aims:Hyponatremia is the predominant electrolyte abnormality with an incidence rate of approximately 22%. It is the leading cause of morbidity and mortality with scarce data in Indian intensive care settings. The aim of this study is to evaluate the clinical features and etiology of hyponatremia in patients admitted to an Intensive Care Unit (ICU) of a tertiary care hospital.Materials and Methods:A 1-year prospective cross-sectional observational study was conducted, including 100 adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
2
20
2
Order By: Relevance
“…The other factor that showed significant association was taking diuretics in which the odds of developing electrolyte disorder were 4.39 higher among patients with diuretics when compared to their counterparts. This was in line with studies conducted in India, Switzerland and Ethiopia [ 38 40 ]. This might be dues to the fact that drugs especially diuretics are a major cause of hyponatremia in DM and hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
“…The other factor that showed significant association was taking diuretics in which the odds of developing electrolyte disorder were 4.39 higher among patients with diuretics when compared to their counterparts. This was in line with studies conducted in India, Switzerland and Ethiopia [ 38 40 ]. This might be dues to the fact that drugs especially diuretics are a major cause of hyponatremia in DM and hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
“…14,15 Previous Indian studies have also reported similar men preponderance above 50 years of age. 6,16 In contrast, few investigations showed that women are generally affected more by hyponatremia than men (52-70%). [17][18][19] The present study revealed 39.3% of study population aged below 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…They reported CNS infections, chronic liver disease and acute gastroenteritis as the common causes of hyponatremia in hospitalized patients and presented with intracranial hemorrhages as seen in this study. 6,16 Although clearly not indicative of the overall prevalence of hyponatremia globally, it has been observed in as high as 42.6% of patients in a large acute care hospital in Singapore and in 30% of patients hospitalized in an acute care setting in Rotterdam. 5,20,21 The most common cause of hyponatremia in the present study was SIADH that was in accordance with the reported studies.…”
Section: Discussionmentioning
confidence: 99%
“…The hyponatremia group a longer stay, longer ventilator days and had more mortality Babaliche P et al [14] (2017) n=100 Prospective cross-sectional study S/S: Vomiting confusion.…”
Section: Studymentioning
confidence: 99%